Analyses of production capacity of 89Sr and 90Sr in the 2 MW molten salt reactor. (July 2021) - Wu, Chen; Yu, Chenggang; Zhang, Ao; Zou, Chunyan; Ma, Yuwen; Wu, Jianhui; Cai, Xiangzhou; Chen, Jingen
Abstract: The production capacity of 89 Sr and 90 Sr in the 2 MW MSR are evaluated. The gaseous 89 Kr and 90 Kr are extracted from the core through the helium bubbling system, and then decay to 89 Sr and 90 Sr, respectively. In order to improve purity of 89 Sr product, two cooling devices are adopted in the 89 Sr and 90 Sr production system. The annual yields of 89 Sr and 90 Sr are about 9000 Ci and 32 Ci, respectively, and the impurity of 89 Sr product is less than 2 ppm which can meet the medical requirement. Highlights: The production capacity of 89 Sr and 90 Sr in the 2 MW Molten Salt Reactor are evaluated and the annual yield of 89 Sr and 90 Sr are about 9000 Ci and 32 Ci, respectively. The production of 89 Sr by the decay chain of 89 Kr-> 89 Rb-> 89 Sr through the helium bubbling system has been assessed. The cooling time of Kr in cooling device 1 is optimized to be 6 min to improve the quality of 89 Sr product.